2010
DOI: 10.1248/bpb.33.580
|View full text |Cite
|
Sign up to set email alerts
|

Invariant V.ALPHA.14 Natural Killer T Cell Activation by Edible Mushroom Acidic Glycosphingolipids

Abstract: Natural killer T (NKT) cells recognize CD1d loaded with glycosphingolipid (GSL) antigens. After being stimulated by GSL antigens, NKT cells immediately secrete cytokines. 2-4)The variety of cytokines release from NKT cells can promote immunoresponses against tumors and microbial infections, and regulate autoimmune responses, 5,6) although a puzzling aspect of these responses is that both Th1 and Th2 cytokines can be secreted in response to the stimulation.The fungal glycolipids are exogenous antigens for NKT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…are widespread throughout the hardwood forests of the world. Many bioactive components derived from Pleurotus are known as antitumor agents, cholesterol reducers, or antioxidative agents and have also been shown to modulate the immune system . Our recent investigations revealed the antitumor property of Pleurotus citrinopileatus .…”
Section: Introductionmentioning
confidence: 94%
“…are widespread throughout the hardwood forests of the world. Many bioactive components derived from Pleurotus are known as antitumor agents, cholesterol reducers, or antioxidative agents and have also been shown to modulate the immune system . Our recent investigations revealed the antitumor property of Pleurotus citrinopileatus .…”
Section: Introductionmentioning
confidence: 94%
“…The antitumor activity increased in a concentrationdependent manner and reached to 61.4% at the concentration of 400 μg/ml. In addition, Ma et al [9] also found polysaccharides in Pleurotus eryngii could suppress the proliferation of HepG-2 cells and enhance lactate dehydrogenase (LDH) in a dose-and time-dependent manner [10][11][12][13][14]. A water-soluble polysaccharide isolated from Pleurotus eryngii significantly suppressed the tumor growth in Renca-bearing mice at the doses of 50, 100 and 200 mg/kg [2].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…They found that the hotwater extract increased significantly in serum IFN-γ levels, the highlevel production of IFN-γ in the culture supernatant from can enhance immunity in the trial immunogen group mice [13]. Furthermore, purified acidic glycosphingolipids (AGLs) from Pleurotus eryngii were reported that AGL could induced interleukin-2 (IL-2) release from invariant natural killer T (iNKT) cells and induced prolonged retention of IL-4 in serum in vitro and in vivo [14]. These indicated that Pleurotus eryngii AGLs might be involved in the maintenance of immunohomeostasis through iNKT cell activation.…”
Section: Immuno-modulating Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the AGLs, a-galactosylceramide (a-GalCer) and isoglobotriaosylceramide (iGb3, Gala1-3Galb1-4Glcb1-1 0 Cer) are also known to activate iNKT cells upon CD1d-mediated stimulation. [16][17][18][19][20] Although the AGLs in edible mushrooms were weaker antigens for iNKT cells than a-GalCer, they may contribute to enhance the immune system as immunomodulatory antigens.…”
Section: Introductionmentioning
confidence: 99%